Photon-counting computed tomography of coronary and peripheral artery stents: a phantom study - Stein, Thomas; Taron, Jana; Verloh, Niklas; Doppler, Michael; Rau, Alexander; Hagar, Muhammad Taha; Faby, Sebastian; Baltas, Dimos; Westermann, Dirk; Ayx, Isabelle; Schönberg, Stefan; Nikolaou, Konstantin; et al. (Scientific reports, 2023)
Accurate small vessel stent visualization using CT remains challenging. Photon-counting CT (PCD-CT) may help to overcome this issue. We systematically investigate PCD-CT impact on small vessel stent assessment compared to energy-integrating-CT (EID). 12 water-contrast agent filled stents (3.0-8 mm) were scanned with patient-equivalent phantom using clinical PCD-CT and EID-CT. Images were reconstructed using dedicated vascular kernels. Subjective image quality was evaluated by 5 radiologists independently (5-point Likert-scale; 5 = excellent). Objective image quality was evaluated by calculating multi-row intensity profiles including edge rise slope (ERS) and coefficient-of-variation (CV). Highest overall reading scores were found for PCD-CT-Bv56 (3.6[3.3-4.3]). In pairwise comparison, differences were significant for PCD-CT-Bv56 vs. EID-CT-Bv40 (p ≤ 0.04), for sharpness and blooming respectively (all p < 0.05). Highest diagnostic confidence was found for PCD-CT-Bv56 (p ≤ 0.2). ANOVA revealed a significant effect of kernel strength on ERS (p < 0.001). CV decreased with stronger PCD-CT kernels, reaching its lowest in PCD-CT-Bv56 and highest in EID-CT reconstruction (p ≤ 0.05). We are the first study to verify, by phantom setup adapted to real patient settings, PCD-CT with a sharp vascular kernel provides the most favorable image quality for small vessel stent imaging. PCD-CT may reduce the number of invasive coronary angiograms, however, more studies needed to apply our results in clinical practice.
Online veröffentlicht: 08. September 2023
Gesehen am 06.12.2023